2017
DOI: 10.1007/s10856-016-5820-4
|View full text |Cite
|
Sign up to set email alerts
|

Peculiarities in thermal evolution of precipitated amorphous calcium phosphates with an initial Ca/P ratio of 1:1

Abstract: Thermal evolution of amorphous calcium phosphate (ACP) powder from a fast nitrate synthesis with a Ca/P ratio of 1:1 were studied in the range of 20-980 °C. The powder consisted of amorphous dicalcium phosphate anhydrate (CaHPO) after heating to 200 °C. CaHPO gradually condensed to amorphous calcium pyrophosphate CaPO (CPP) between 200 to 620 °C. Amorphous CPP crystallized at 620-740 °C to a metastable polymorph α'-CPP of the high-temperature phase α-CPP and β-CPP. The α'-CPP/ β-CPP phase ratio reached a maxim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 26 publications
0
11
0
Order By: Relevance
“…Formation of calcium phosphate (CP) with a higher Ca/P ratio than the given in mother solution (for Ca/P < 1) Z.Z. Zyman et al / Processing and Application of Ceramics 11 [2] (2017) 147-153 was also observed earlier [14] under the conditions similar to those in the study [13]. However, no explanation was proposed [14] for this effect.…”
Section: Introductionmentioning
confidence: 82%
See 2 more Smart Citations
“…Formation of calcium phosphate (CP) with a higher Ca/P ratio than the given in mother solution (for Ca/P < 1) Z.Z. Zyman et al / Processing and Application of Ceramics 11 [2] (2017) 147-153 was also observed earlier [14] under the conditions similar to those in the study [13]. However, no explanation was proposed [14] for this effect.…”
Section: Introductionmentioning
confidence: 82%
“…A powder from the process consists of large particles with high crystallinity, which significantly reduces its bioactivity compared to a nanocrystalline one [9][10][11][12]. It was recently observed that fine-grained α ′ -and β-CPPs and small amount of β-TCP can be formed from ACP powder with a Ca/P ratio of 1 : 1 using a fast variation of the nitrate synthesis upon heating above 800°C [13]. β-TCP is well known due to excellent bioactivity [12], so its presence may improve the biological performance of the CPPs.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…], as reported for many pyrophosphate materials [41,42]. The rst was attributed to the amorphous CPP and the second to crystalline CPP.…”
Section: -mentioning
confidence: 60%
“…[11][12][13][14]. The formation of these phosphates was affected from a Ca/P mixing ratio of raw materials, heating temperature and time, additives, and so on [15][16][17]. Further, phosphate materials produce condensed phosphate in a dehydration reaction [18,19].…”
Section: Introductionmentioning
confidence: 99%